Changes in the numbers of patients with acute gastroenteritis after voluntary introduction of the rotavirus vaccine in a Japanese children’s primary emergency medical center - Ichiro Morioka; Naohiro Kamiyoshi; Masahiro Nishiyama; Tomohiko Yamamura; Shogo Minamikawa; Sota Iwatani; Hiroaki Nagase; Kandai Nozu; Noriyuki Nishimura; Mariko Taniguchi-Ikeda; Kazuto Ishibashi; Akihito Ishida; et al. (Environmental Health and Preventive Medicine, 2017)
Abstract Background Acute gastroenteritis (AGE) is a major reason for presentation to pediatric primary emergency medical centers. Because rotavirus vaccines were introduced in November 2011 for voluntary vaccination in Japan, we analyzed the changes in the numbers of AGE patients. Methods The number and proportion of patients visiting Kobe children’s primary emergency medical center from January 2011 to February 2015 due to AGE, out of all visiting children, were investigated retrospectively. The rotavirus and norovirus epidemic periods were defined as the periods from March to June and from November to February, respectively, based on their disease prevalence. Results In patients ≤2 years of age, the numbers and proportions of patients with AGE were significantly decreased from 2464/14098 (17%) in 2011 to 1888/12321 (15%) in 2014 (p < 0.01). In patients ≤2 and 3–5 years of age, significant decreases in AGE patients between 2011 and 2014 were observed during the rotavirus season (from 20% [1090/5329] to 14% [642/4482] in patients aged ≤2 years and from 23% [704/3047] to 20% [572/2807] in patients aged 3–5 years, p < 0.01 and p < 0.05, respectively), but not during the norovirus season (from 19% [834/4436] to 19% [797/4160] in patients aged ≤2 years and from 20% [679/3334] to 25% [710/2852] in patients aged 3–5 years). Conclusions The estimated rotavirus vaccine coverage in our area increased from 1% in 2011 to 49% in 2014; this coverage may have resulted in a reduction in AGE patients, both directly and indirectly, in our Japanese children’s primary emergency medical center.